Mythical imaginary in rural agricultural practices on properties of La Vieja river basin, Colombia - Ramírez Arias, Sebastián; Zúñiga Torres, María Constanza; Quintero Vargas, Heimar; Jiménez García, Williams Gilberto (Centro de Historia Argentina y Americana, 2010)
This work analyzes the mythological belief or superstitions associated with farming and conservation activities in nine rural productive units on the river basin La Vieja, Colombia. The elderly people recognize the influence of multiple stories over productive and environmental conditions that are an important part of success or fail on their rural activities. The beliefs were classified by their functionality and the activities they regulate. 14 myths that have any on the influence activities of cultivate, breeding, conservation and social regulation were described. The main element for discussion was the functionality, considering its relationship the distribution and application in the subsystems of productions in the farms with the age, the gender and the hierarchy position on the family structure. It was conclude that the flow of information between expert systems and systems of popular knowledge helps to construct an adapted system. An example is the use, in cattle farms, of different moon phases during the artificial insemination to ensure the pregnancy and sex of the breed.